Brief cognitive-behavioral training for tinnitus relief using a mobile application: A pilot open trial. (14th March 2022) - Oron, Yahav; Ben David, Boaz M; Doron, Guy
Background: Tinnitus may be a disabling, distressing disorder whereby patients report of sounds, in the absence of external stimulus. Recent evidence supports the effectiveness of psychological interventions, particularly, cognitive behavioral therapy (CBT) based intervention for the reduction of tinnitus-related distress and disability. This study assessed the effectiveness of mobile delivered cognitive training exercises to reduce tinnitus-related distress. Materials and Methods: Out of 26 patients diagnosed with tinnitus, 14 participants completed all 48 levels of the app. Levels of pre-post intervention tinnitus intrusiveness and handicap were evaluated using the short Hebrew version of the Tinnitus Handicap Inventory (H-THI). Mood was assessed using a Visual Analogue Scale (VAS). Participants were instructed to complete 3–4 min of daily training for 14 days. Results: Repeated-measures ANOVA of completers showed a significant large-effect size reduction on H-THI scores. 50% of completers have shown reliable change (indicated by their Reliable Change Index [RCI] scores). No significant change was found in mood. Discussion: Several minutes a day of training using a CBT-based app targeting maladaptive believes may decreased patients' tinnitus intrusiveness and handicap. Conclusions: Mobile apps can provide access to CBT-based interventions, using an efficient, inviting and simple platform, addressing the ramifications of tinnitus symptoms.